High rate of multi-drug resistant Escherichia coli isolated from patients with urinary tract infections in Ifakara-Tanzania: implications for empirical antibiotic treatment guidelines and stewardship programs - Magreth Erick Macha; Philipp Kohler; Anja Bösch; Honorathy Msami Urassa; Weihong Qi; Salome N. Seiffert; Sabine Haller; Erin West; Maja Weisser Rohacek; Baharak Babouee Flury (Antimicrobial Resistance and Infection Control)
Abstract Background Antimicrobial resistance (AMR) in Sub-Saharan Africa is a significant health threat, with limited data guide treatment. This study investigates multi-drug resistant Escherichia coli in urinary tract infections (UTIs) in rural Tanzania to guide empirical treatment strategies. Methods A cross-sectional prospective study of adults with UTIs was conducted at St. Francis Regional Referral Hospital in Ifakara, Tanzania, from September 2021 to August 2023. Urine culture isolates underwent routine diagnostics in Tanzania and E. coli isolates underwent whole-genome sequencing in Switzerland. Results Of 1055 patients, 248 (23.5%) had positive urine cultures, with E. coli as predominant pathogen (n = 87; 55.7%). Extended-spectrum beta-lactamase-producing E. coli (ESBL-E) was identified in 20 (23.0%) isolates, primarily sequence type ST167 carrying CTX-M-27. All ESBL-E cases (20/20, 100.0%) and half of non-ESBL-E cases (29/58, 50.0%) received empiric antibiotics to which the isolates were documented as resistant. ESBL-E showed higher resistance to cotrimoxazole (100.0%) and ciprofloxacin (90.0%) latter recommended for complicated UTIs in Tanzania’s Standard Treatment Guidelines (STG) compared to non-ESBL-E. All ESBL-E isolates were susceptible to nitrofurantoin, as recommended by STG for uncomplicated UTIs, and fosfomycin showed potential alternative for complicated cases. Conclusion Nearly one-quarter of E. coli isolates causing UTIs were ESBL-E, predominantly ST167 harboring bla CTX−M−27. Notably, nitrofurantoin remained effective for uncomplicated UTIs, similarly, fosfomycin emerged as a viable alternative. However, ciprofloxacin, despite being recommended in local guidelines for complicated UTIs, showed no efficacy. The genetic similarity between human and environmental isolates underscores the critical need for a One Health approach to tackle antimicrobial resistance (AMR) in the region.